A visão das mulheres empreendedoras no mercado municipal de araguaína sobre o plano nacional de políticas públicas. - Castro, Vanessa Gomes de (Universidade Federal do Tocantins, 2023)
This study aims to report the vision of women entrepreneurs in the municipal market Araguaína-TO on the national plan of public policies for women. Thus, it appears, through literature review, as developed women's labor relations, as well as their greater participation in the historical context of the Industrial Revolution. It sought to delineate a general explanation about the National Policy for Women Plan, with a focus on public policies to promote the labor market to provide greater integration of women in this context, as well as other policies that support their stay through training programs and social inclusion, based on the investigation of the scope of public policy contained in the Plan. Through experience reports made in the municipal market Araguaína, which were recorded and then transcribed, knew a little of the reality of these, as well as their knowledge of the benefits that the national plan for public policies bring to women. According to the analysis results, it was noted that 55.55% of them work an average of twenty years in the market, and mostly (77.77%) are satisfied with their work, which is their main source of income, while 88.88% of them do not know the policies that are explained in the PNPM, and only 11.11% had access to programs such as My home, my life. Thus, this work can contribute in the statement of support failure of public policy, pointing out deficiencies, so that all efforts can reach those who really need.